Effect of Doping Position on the Active Silicon-on-Insulator Micro-Ring Resonator Based on Free Carrier Injection - Mardiana, Bidin; Sahbudin, Saari; Menon, P.S; Haroon, Hazura; Hanim , Abdul Razak (Science Publications, 2012)
Problem statement: Metal interconnects have become significant limitation on the scaling of CMOS technologies in electronics integrated circuit. Silicon photonics has offers great potential to overcome this critical bottleneck due to the advantages of optical interconnects. Silicon-based optical micro-ring resonator is promising basic element of future electronic-photonic integrated circuits because of its wide applications on photonic devices such as modulator, switch and sensor. Approach: This study highlights the study of the free carrier injection effect on the active SOI micro-ring resonator. The effect of the free carrier injection on micro-ring resonator is evaluated by varying the p+ and n+ doping position. Device performances are predicted using numerical modeling software 2D SILVACO as well as Finite Difference Time Domain (FDTD) simulation software, RSOFT. Results: The results show that the refractive index change increases as the p+ and n+ doping position become closer to the rib waveguide. A shift in resonant wavelength of around 2 and 3 nm was is predicted at 0.9V drive forward voltage for 0.5 and 1.0 Î¼m gap distance between p+ and n+ doping regions and the sidewall of the rib waveguide. It is also shown that 10 and 9.2 dB maximum change of the output response obtained through the output of the transmission spectrum of the device with gap 0.5 and 1.0 Î¼m. Conclusion: The closer distance between p+ and n+ doping regions and the rib waveguide has optimal shift of resonance wavelength and better extinction ratio of transmission spectrum.